Development of a Scale for Measuring the Competencies of Islamic Counselors - Imas Kania Rahman; Noneng Siti Rosidah; Abas Mansur Tamam (Islamic Guidance and Counseling Journal, 2023)
The competence of an individual's personality is a crucial aspect in determining the success of guidance and counseling services. It is important to measure the personality competence of Islamic counselors to assess their preparedness to fulfill their responsibilities in the workplace. This measurement serves as a benchmark for the quality of prospective Islamic counselors and can be used as an evaluation tool. The objective of this study is to develop a scale to measure the personality competence of prospective Islamic counselors based on the American School Counselor Association (ASCA), the American Counseling Association (ACA), and the Minister of National Education Regulation of the Republic of Indonesia Number 27 Year 2008 related to counselor competencies. The study employed a qualitative approach in formulating statement items and a quantitative approach to test the internal validity of the scale. The internal validity was confirmed through V-Aiken analysis and Confirmatory Factor Analysis (CFA) using the Kaiser Meyer Olkin (KMO) test. Additionally, the reliability of the scale was tested using the Cronbach Alpha method. The results showed that the Islamic counselor personality competence scale was declared to be valid and reliable for all indicators and items.